Species and trichothecene genotypes within Fusarium incarnatum-equiseti species complex infecting Brazilian rice - Avila, Caroline Fernanda de (2017)
Brazil is a major producer and consumer of rice. Fusarium species infect and colonize cereal grains, and some are able to produce harmful mycotoxins that can accumulate in the kernels. Species of Fusarium incarnatum-equiseti species complex (FIESC) are regularly detected in rice kernels and are known as producers of different mycotoxins. The present study aimed to identify the phylogenetic species, evaluate the potential for trichothecene production and morphological variation of the FIESC strains associated with Brazilian rice kernels. An initial set of 147 FIESC strains were isolated from rice kernels produced at all major rice-growing regions in the country. A subsample (67 isolates) representative of all regions was subjected do DNA extraction followed by amplification and sequencing of a portion of the translation elongation factor 1-α (EF-1α) gene. The DNA sequences alignment of FIESC isolates and reference strains were subjected to Bayesian inference, maximum parsimony and maximum likelihood. Microscopic characters were conducted with cultures grown on SNA at 25 oC in 12 h photoperiod. Radial growth and colony pigmentation were evaluated on PDA at 25 oC in complete darkness for 3 and 14 days, respectively. Toxigenic potential was assessed by the detection of terpene synthase (Tri5) gene by PCR. Phylogenetic analysis suggested the presence of 15 species, among them, eight corresponding to previously described species: FIESC 4 (F. lacertarum), 6, 16, 17, 20, 24, 26 and 29. Seven new phylogenetic species were proposed: FIESC 32−38. Among them, six were constituted by a single strain. Thirty-one Tri5+ isolates were found in 46.2% of species, including the two most dominant species, FIESC 26 and 32, and were distributed randomly across geographic regions. Morphological traits were observed and measured, and differences among morphological characteristics allowed distinguishing the patterns found in this study. Our results provide a baseline data on morphology of FIESC species, as well as an improved understanding of the composition and toxigenic potential of species within this complex associated with Brazilian rice.